Teachers’ Readiness in Implementing the Flipped Classroom Method Using Technology and Non-Technology Approach in Chemistry Education - Lutfiana Ufiqoh; Habiddin Habiddin; Ridwan Joharmawan; Shinta Permata Sari (J-PEK (Jurnal Pembelajaran Kimia), 2026)
The study aims to analyse teachers’ readiness to implement the flipped classroom method in chemistry education, using both technological and non-technological approaches, through a systematic literature review (SLR). Twelve high-quality articles published in reputable journals over the last five years were analysed. The findings indicate that flipped classroom implementation in chemistry education predominantly employs web-based technologies, such as learning management systems. Instructional videos and online collaborative platforms. Teachers’ readiness in technology-based approaches is characterised by digital literacy and the ability to integrate technology into instructional design. Meanwhile, teachers’ readiness in non-technology-based approaches emphasises content mastery, pedagogical competence, and effective face-to-face classroom management. The results also reveal differences in teachers’ readiness between technology-based flipped classroom approaches, particularly in learning adaptation and the use of instructional media. This study recommends that future research further explore instructional strategy development and provide comprehensive solutions to challenges in implementing flipped classroom learning in chemistry education.